LANGUAGE COMPETENCE OF ASD’S CHILDREN AGE 0-5 YEARS: STUDY OF AUTISTIC CHILDREN LANGUAGE ACQUISITION : [KEMAMPUAN BAHASA ANAK DENGAN GANGGUAN SPEKTRUM AUTISME (GSA) USIA 0-5 TAHUN: STUDI TENTANG PERKEMBANGAN BAHASA PADA ANAK AUTIS] - Astria Prameswari (Universitas Pelita Harapan, 2026)
Autism Spectrum Disorder (ASD) is a neurological condition in the brain. One symptom easily observed is the presence of language disorders that cause language deficiency. This study aims to provide initial knowledge as a foundation for developing language learning for children with ASD. The study was longitudinal, involving 1 (one) child with ASD aged 5 years old in Indonesia (S), as the sample. Psycholinguistics was used as a fundamental theory to interpret language disorders in children with ASD. Our findings show that the language competence of the child with ASD (S) begins to experience deficiency when the child enters the age of 2 years. At the age of 4 years old, the language competence begins to emerge through nonverbal communication. Verbal competence appears at age 5, marked by pronouncing one vowel sound /a/ and /u/ to name objects. S’s nonverbal competence in this period also appears in communication responses to other people. Other language characteristics for S, such as echolalia also appear in his language profile. Abstrak Bahasa Indonesia Gangguan Spektrum Autisme (GSA) adalah suatu kondisi neurologis pada otak. Salah satu gejala yang mudah diamati adalah adanya gangguan bahasa yang menyebabkan keterbatasan bahasa. Penelitian ini bertujuan untuk memberikan pengetahuan awal sebagai landasan dalam mengembangkan pembelajaran bahasa bagi anak-anak dengan GSA. Penelitian ini bersifat longitudinal, dengan melibatkan 1 (satu) anak dengan GSA berusia 5 tahun di Indonesia (S) sebagai sampel. Psikolinguistik digunakan sebagai teori dasar untuk menafsirkan gangguan bahasa pada anak-anak dengan ASD. Temuan kami menunjukkan bahwa kompetensi bahasa anak dengan ASD (S) mulai mengalami kekurangan saat anak memasuki usia 2 tahun. Pada usia 4 tahun, kompetensi bahasa mulai muncul melalui komunikasi nonverbal. Kompetensi verbal muncul pada usia 5 tahun, yang ditandai dengan pengucapan satu bunyi vokal /a/ dan /u/ untuk menyebut nama benda. Kemampuan nonverbal S pada periode ini juga terlihat dalam respons komunikasinya terhadap orang lain. Karakteristik bahasa S lainnya, seperti echolalia, juga terlihat dalam profil bahasanya.